Antibacterial activity of 3-methylbenzo[d]thiazol-methylquinolinium derivatives and study of their action mechanism - Ning Sun; Ruo-Lan Du; Yuan-Yuan Zheng; Qi Guo; Sen-Yuan Cai; Zhi-Hua Liu; Zhi-Yuan Fang; Wen-Chang Yuan; Ting Liu; Xiao-Mei Li; Yu-Jing Lu; Kwok-Yin Wong (Taylor & Francis Group, 2018)
The increasing incidence of multidrug resistant bacterial infection renders an urgent need for the development of new antibiotics. To develop small molecules disturbing FtsZ activity has been recognized as promising approach to search for antibacterial of high potency systematically. Herein, a series of novel quinolinium derivatives were synthesized and their antibacterial activities were investigated. The compounds show strong antibacterial activities against different bacteria strains including MRSA, VRE and NDM-1 Escherichia coli. Among these derivatives, a compound bearing a 4-fluorophenyl group (A2) exhibited a superior antibacterial activity and its MICs to the drug-resistant strains are found lower than those of methicillin and vancomycin. The biological results suggest that these quinolinium derivatives can disrupt the GTPase activity and dynamic assembly of FtsZ, and thus inhibit bacterial cell division and then cause bacterial cell death. These compounds deserve further evaluation for the development of new antibacterial agents targeting FtsZ.